Questions of the actualization economic evaluation of lands - Kovalyshyn, O.; Malakhova, S.; Ryzhok, Z. (Land Management, Cadastre and Land Monitoring, 2018)
The Law "On land evaluation" has approved three types of evaluation: soil rating, economic, monetary, which is divided into normative and expert. Each of them characterizes, according to certain indicators, the quality of the soil and the productivity of agricultural land, determines the value and has its purpose. We want to dwell on the economic evaluation of land, which allows us to assess it from the position of the main means of production in agriculture. The last of its indicators were approved in 1988 and it becomes obvious that they do not meet the current conditions of agriculture and are outdated. Under these conditions, the updating of economic land valuation data becomes relevant. Analysis of recent researches and publications. In their scientific studies Dehtyarenko Yu., Dobryak D., Drapikovsky O., Zayats V., Mantsevich Yu.,Tretyak A., Martin A., Mykula O. and other scholars recognize the need to improve the methodological principles of economic evaluation of agricultural land in modern economic conditions. The purpose of the study is to update the indicators of economic land evaluation in accordance with the results of agricultural enterprises. Results of the researches and their discussion. A comparative assessment in absolute terms (UAH / ha) based on the results of the production of grain crops by agricultural enterprises in the Lviv region for 2015 and the relative values (points) based on the data of the economic appraisal of land in 1988, which makes it possible to detect differences in the economic fertility of the soil are given in Table 1. • 1. Economic evaluation of arable land by the results of production of grain and leguminous crops by agricultural enterprises in Lviv region for 2015 Administrative-territorial area Cost of gross output Payback costs Differential income UAH/ha Pnts. UAH/100 UAH Pnts. UAH/ha Pnts. Brody 21585,15 54 169,03 67 4345,15 41 Busk 14251,78 55 123,25 63 -1359,26 40 Horodok 10688,38 37 98,66 53 -3937,49 18 Drohobych 9916,54 48 118,07 62 -1421,68 34 Zhydachiv 13815,14 43 141,73 54 656,21 25 Zhovkva 9631,87 45 128,86 52 -458,78 26 Zolochiv 14322,09 56 127,52 66 -839,65 43 Kamianka-Buzka 22269,46 52 123,39 61 -2096,01 36 Mykolayiv 11007,56 43 105,13 59 -3127,50 29 Mostyska 10792,59 40 119,26 58 -1424,69 26 Peremyshlyany 15026,66 35 141,25 47 664,44 16 Pustomyty 12385,12 53 142,52 65 653,73 40 Radekhiv 20795,08 47 116,72 61 -3255,95 33 Sambir 4982,69 45 174,62 57 1130,46 29 Skole 5184,34 30 120,62 43 -617,82 12 Sokal 12073,94 54 133,60 63 -126,25 39 StaryySambir 6731,40 35 104,64 54 -1953,02 21 Stryi 14646,27 39 69,97 57 -13612,60 25 Turka 5100,77 31 134,78 46 -8,45 14 Yavoriv 6167,76 35 135,32 49 14,72 18 Lviv region 16604,95 47 125,35 60 -1278,57 32 On the basis of the analysis of residue distribution in the Statistica program, the points of economic land evaluation, which correspond to its actual indicators, which we obtained on the basis of statistical information on the results of production of grain and leguminous crops by agricultural enterprises in the Lviv region for 2015, were calculated (Table 2). • 2. Results of the economic evaluation for the cultivation of grain and leguminous crops by agricultural enterprises in the Lviv region for 2015 Administrative-territorial area Total economic evaluation of land, points Cost of gross output Payback costs Differential income 1988 2015 1988 2015 1988 2015 Brody 54 53 67 58 41 31 Busk 55 46 63 57 40 28 Horodok 37 43 53 56 18 27 Drohobych 48 42 62 57 34 28 Zhydachiv 43 46 54 57 25 29 Zhovkva 45 42 52 57 26 29 Zolochiv 56 46 66 57 43 28 Kamianka-Buzka 52 54 61 57 36 28 Mykolayiv 43 43 59 56 29 27 Mostyska 40 43 58 57 26 28 Peremyshlyany 35 47 47 57 16 29 Pustomyty 53 44 65 57 40 29 Radekhiv 47 52 61 57 33 27 Sambir 45 37 57 58 29 29 Skole 30 37 43 57 12 29 Sokal 54 44 63 57 39 29 StaryySambir 35 39 54 56 21 28 Stryi 39 46 57 55 25 23 Turka 31 37 46 57 14 29 Yavoriv 35 38 49 57 18 29 Lviv region 47 60 32 Conclusions and perspectives. In order to update the data of the economic evaluation of land in modern economic conditions, we calculated the differential income, which depends on the yield, costs and prices for the sale of grain crops. As a result of the study, negative differential indices were obtained, which were compared with the 1988 economic appraisal marks and the official statistical data of agricultural production indicators. In order to analyze the data obtained, we create an economic-mathematical model in the form of a regression equation, which reflects the relationship between the points of the economic evaluation of land in 1988 and its actual indicators. However, there is no expected relationship between them. We propose new points for economic land evaluation that reflect the real results of grain and legume production by analyzing the remnants of the correlation-regression analysis. Key words: economic evaluation of lands, differential income, cost of production, selling price, profitability level, correlation-regression analysis, analysis of residues.